Development of guidelines for the management of groundwater in and around rehabilitated coal discard facilities - Myburgh, Duheine (University of the Free State, 2017)
No abstract
Dissertation (M.Sc. (Institute for Groundwater Studies))--University of the Free State, 2017
Keywords: Groundwater -- Quality -- South Africa; Coalfields -- South Africa; Groundwater -- South Africa; Coal mines and mining -- Environmental aspects -- South Africa; Mine water -- South Africa